Rotating Biological Contactors (RBC's). Student Manual. Biological Treatment Process Control - Zickefoose, Charles S.; Linn-Benton Community Coll., Albany, OR. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
This student manual provides the textual material for a unit on rotating biological contactors (RBC's). Topic areas considered include: (1) flow patterns of water through RBC installations; (2) basic concepts (shaft and stage); (3) characteristics of biomass; (4) mechanical features (bearings, mechanical drive systems, and air drive systems); (5) design considerations (flow rates, organic and solid loads, industrial loading, and weather/environmental influences); (6) interaction of unit processes (preliminary treatment, primary clarifier, return streams, and secondary clarifier); (7) process monitoring and testing, focusing on the visual observation of the biomass; (8) process control for steady state operation (considering mechanical and air drive systems); and (9) making process control changes. A list of objectives, a glossary of key terms, a list of references, and student worksheets are included. It is assumed that students using this manual have had some experience in wastewater treatment and a basic understanding of biological treatment. (JN)
Availability: Linn-Benton Community College, 6500 S.W. Pacific Blvd., Albany, OR 97321.
Sponsoring Agency: Environmental Protection Agency, Washington, DC. Office of Drinking Water.
Contract Number: EPA-T901238.
ERIC Note: For related documents, see SE 045 333-353.
Educational level discussed: Postsecondary Education.
Students.
Keywords: Biology; Laboratory Procedures; Postsecondary Education; Sludge; Training Methods; Waste Disposal; Waste Water; Water Treatment; Rotating Biological Contactors; Unit Processes; Guides, Classroom -- Learner